Determinants of infant mortality level in chosen African countries - Morkusová, Andrea; Miskolczi, Martina; Pavlík, Petr, 1957-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
The aim of the diploma thesis is to analyse which determinants have an impact on infant mortality in West and East Africa for a year 2012 based on correlation and regression analysis. Representative countries Ghana, Nigeria and Senegal for West Africa and Kenya, Tanzania and Uganda for East Africa, were chosen. From the gained results and information, recommendation for possible better future development of infant mortality is concluded as the outcome of the diploma thesis aim. On base of data analysis, one variable, which influences a development of infant mortality, was not identified, but it can be assumed that a complex of variables affects the infant mortality. In this line with final findings, current strategy of development aid is focused primarily on local activities more than just on financial help.
Vedoucí práce: Martina Miskolczi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomická demografie [obor dipl. práce]; diplomové práce; master's theses